Penggunaan dan Pemanfaatan Teknologi pada Generasi Digital - Asnawati Asnawati; Indra Kanedi; Venny Novita Sari; Ricky Zulfiandry; Desi Mahdalena (Jurnal Dehasen Untuk Negeri, 2024)
The importance of using and utilizing technology to increase knowledge in the Generation Z era among youth is one of the driving factors to remain competitive in the digital world. With this digital technology, it is easier for all groups to access information on social media such as Google, YouTube, ChatGPT. Analysis of the situation with partners, in this case SMA Negeri 1 Kepahiang, revealed a picture of students' lack of understanding of the development of information technology, especially in the digital field. so that the school conveyed the need to socialize the technology directly to the students of SMAN 1 Kepahiang. Parts of the field of computer science that continue to develop include artificial intelligence as a tool and a substitute for human functions, one of which is ChatGPT technology which is an artificial intelligence-based machine technology that is trained to be able to imitate human conversation using NPL (Natural Language Processing) technology. And used to produce quite scientific writing or even books with prompts. So that opportunities for innovation using this technology are wide open for education in Indonesia, one of which is improving the writing skills of students in schools/campuses to achieve the six competencies (critical thinking, collaboration, communication, creativity, character education and citizenship) that are needed in the current era. This. In this case, this service effort is carried out to provide generation Z with more in-depth knowledge regarding artificial intelligence and prepare them to be able to keep up with technological developments that continue to develop